Combined effects of overweight and smoking in late adolescence on subsequent mortality: nationwide cohort study. (24th February 2009) - Neovius, Martin; Sundström, Johan; Rasmussen, Finn
Abstract : Objective To investigate the combined effects on adult mortality of overweight and smoking in late adolescence. Design Record linkage study with Cox proportional hazard ratios adjusted for muscle strength, socioeconomic position, and age. Setting Swedish military service conscription register, cause of death register, and census data. Participants 45 920 Swedish men (mean age 18.7, SD 0.5) followed for 38 years. Main outcome measures Body mass index (underweight (BMI <18.5), normal weight (18.5-24.9), overweight (25-29.9), and obesity (≥30)), muscle strength, and self reported smoking (non-smoker, light smoker (1-10 cigarettes/day), heavy smoker (>10/day)) at mandatory military conscription tests in 1969-70. All cause mortality. Results Over 1.7 million person years, 2897 men died. Compared with normal weight men (incidence rate 17/10 000 person years, 95% confidence interval 16 to 18), risk of mortality was increased in overweight (hazard ratio 1.33, 1.15 to 1.53; incidence rate 23, 20 to 26) and obese men (hazard ratio 2.14, 1.61 to 2.85; incidence rate 38, 27 to 48), with similar relative estimates in separate analyses of smokers and non-smokers. No increased risk was detected in underweight men (hazard ratio 0.97, 0.86 to 1.08; incidence rate 18, 16 to 19), though extreme underweight (BMI <17) was associated with increased mortality (hazard ratio 1.33, 1.07 to 1.64; incidence rate 24, 19 to 29). The relative excess risk due to interaction between BMI and smoking status was not significant in any stratum. Furthermore, all estimates of interaction were of small magnitude, except for the combination of obesity and heavy smoking (relative excess risk 1.5, −0.7 to 3.7). Compared with non-smokers (incidence rate 14, 13 to 15), risk was increased in both light (hazard ratio 1.54, 1.41 to 1.70; incidence rate 15, 14 to 16) and heavy smokers (hazard ratio 2.11, 1.92 to 2.31; incidence rate 26, 24 to 27). Conclusions Regardless of smoking status, overweight and obesity in late adolescence increases the risk of adult mortality. Obesity and overweight were as hazardous as heavy and light smoking, respectively, but there was no interaction between BMI and smoking status. The global obesity epidemic and smoking among adolescents remain important targets for intensified public health initiatives.